2016
DOI: 10.1097/aog.0000000000001396
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Use After Nonserous Epithelial Ovarian Cancer

Abstract: After treatment for nonserous epithelial ovarian cancer, hormone therapy is not associated with decreased disease-free or overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Two randomized trials as well as prospective and retrospective cohort and case-control studies have shown no adverse effect menopausal hormone therapy on survival in women who have been treated for ovarian cancer 49–55. They used a variety of regimens: estrogen alone or combined with a progestogen or testosterone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two randomized trials as well as prospective and retrospective cohort and case-control studies have shown no adverse effect menopausal hormone therapy on survival in women who have been treated for ovarian cancer 49–55. They used a variety of regimens: estrogen alone or combined with a progestogen or testosterone.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study using the Manitoba Cancer Registry and Drug Program Information Network of 357 women found that use of menopausal hormone therapy (n=94) for non-serous epithelial ovarian cancer was not associated with harm and did not decrease overall or disease-free survival 55. It found that in menopausal hormone therapy users under 55 years of age, disease-free survival was longer but there was no statistical difference in overall survival for this age group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian cancer (OC) is the fth leading cause of cancer-related death among women in the world, which has the highest mortality rate of all gynecologic neoplasms (Galdiero et al 2015). Although remarkable advances in the surgery, chemotherapy and radiotherapy progress have been made, the overall OC survival rate has not improved in the past decades (Power et al 2016;Zhou et al 2017). Therefore, it's urgent to develop novel, evidence-based and safe approaches for its prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is the fifth most common cause of cancerassociated mortality in females worldwide, and 90% of cases of ovarian cancer are epithelial-derived malignancies (1). Although ovarian cancer has an improved response to chemotherapy, the prognosis of patients with ovarian cancer is not ideal clinically, with very low survival rate (2,3). Studies have indicated that clinical pathological parameters, including age, tumor stage, patient's body function and residual tumor volume, are independent predictors of the prognosis of ovarian cancer (1-3); however, for patients with similar status and treatments, their survival rates were not the same (4).…”
Section: Introductionmentioning
confidence: 99%